2013
DOI: 10.1002/eji.201243262
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis‐specific CD8+ T cells are functionally and phenotypically different between latent infection and active disease

Abstract: Protective immunity to Mycobacterium tuberculosis (Mtb) remains poorly understood and the role of Mtb-specific CD8 + T cells is controversial. Here we performed a broad phenotypic and functional characterization of Mtb-specific CD8 + T cells in 326 subjects with latent Mtb infection (LTBI) or active TB disease (TB). Mtb-specific CD8 + T cells were detected in most (60%) TB patients and few (15%) LTBI subjects but were of similar magnitude. Mtb-specific CD8 + T cells in LTBI subjects were mostly T EMRA cells (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
129
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 49 publications
(80 reference statements)
21
129
0
2
Order By: Relevance
“…1C), thus indicating a shift to terminal differentiation among total CD8 + T cells in coinfected patients. These results are in line with the effect of Mtb infection on CD8 + T-cell differentiation toward an effector phenotype proposed previously [11].In order to establish whether the differences observed in circulating effector/memory subset proportions occurred due to alterations in the differentiation path, we evaluated transitions between effector/memory subsets by analyzing the correlation between phenotype proportions as described elsewhere [21,24]. A statistically significant negative correlation between the proportions of two given subsets suggests that transitions between those populations are likely to occur.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…1C), thus indicating a shift to terminal differentiation among total CD8 + T cells in coinfected patients. These results are in line with the effect of Mtb infection on CD8 + T-cell differentiation toward an effector phenotype proposed previously [11].In order to establish whether the differences observed in circulating effector/memory subset proportions occurred due to alterations in the differentiation path, we evaluated transitions between effector/memory subsets by analyzing the correlation between phenotype proportions as described elsewhere [21,24]. A statistically significant negative correlation between the proportions of two given subsets suggests that transitions between those populations are likely to occur.…”
supporting
confidence: 92%
“…At present, this is the first report addressing Mtb-specific cytotoxic CD8 + T-cell responses and their memory status in HIV-TB coinfected patients. In TB patients, Rozot et al ascertained that Mtb-specific CD8 + T cells were mostly T EM cells [11]. On the other hand, Caccamo et al studied the phenotype of Mtb-specific CD8 + T cells by tetramer staining in TB patients, and observed a predominance of T CM and lower T TE CD8 + T cells, both of which were reverted after anti-TB therapy [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most reports on host immune responses to TB have focused on CD4 + , CD8 + T cells are important for long-term responses [33,34]. Interestingly, in this study, CD8 + T cells showed the greatest differential responses between the groups before treatment suggesting that they might be more sensitive to changes in the bacteria load with treatment than CD4 + T cells as previously shown [25,34].…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, this profile was mycobacterialantigens-specific as stimulation with PHA (mitogen) showed no differences between the groups. A higher proportion of single-TNF-α producing CD4 + and CD8 + T cells in active TB patients compared with latent TB infected (LTBI) or treated patients is well documented, with high single-TNF-α production associated with active TB disease [18][19][20][21][22][23][24][25]. TNF-α controls MTBC infection progression to disease as evidenced by the increase incidence of active TB in patients treated with anti-TNF-α [26,27].…”
Section: Discussionmentioning
confidence: 99%